A link between DNA double‐strand breaks and regulation of global translation. (25th February 2022) - Kathjoo, Muntaish Bashir; Srivastava, Mrinal
Abstract : In response to double‐strand breaks (DSBs) in the DNA, cells undergo transcriptional, translational and post‐translational reprogramming to tackle the damage. In this study by Riepe et al., the authors have shown that the global translation inhibition of proteins is concomitant to DNA damage response. Treatment with various DSB‐generating agents can cause a major downregulation in the translation of cellular proteins except for the ISR (integrated stress response) proteins. Authors report a specific and significant reduction in the level of a core ribosomal RPS27A protein coupled to kinetics of DSB induction and repair. The study proposes that molecular alterations generated as a by‐product of DNA damage may inadvertently impact phenotypic responses of the cells and a cautious approach must be followed when utilizing DSB‐based genome editing techniques. Comment on: https://doi.org/10.1111/febs.16321 Abstract : DNA double‐strand breaks (DSBs) are one of the most deleterious types of cellular damage. DSBs are a crucial intermediate of gene editing methods and used also for sensitizing cancer cells. Riepe et al. investigated the association of global inhibition of translation to the DSB‐induced DNA damage response. Their work shows loss of RPS27A and significant downregulation in the translation of cellular proteins coupled to DSB induction and repair kinetics. Comment on: https://doi.org/10.1111/febs.16321